PACAP in hypothalamic regulation of sleep and circadian rhythm: importance for headache - Philip R. Holland; Mads Barloese; Jan Fahrenkrug (The Journal of Headache and Pain, 2018)
Abstract The interaction between sleep and primary headaches has gained considerable interest due to their strong, bidirectional, clinical relationship. Several primary headaches demonstrate either a circadian/circannual rhythmicity in attack onset or are directly associated with sleep itself. Migraine and cluster headache both show distinct attack patterns and while the underlying mechanisms of this circadian variation in attack onset remain to be fully explored, recent evidence points to clear physiological, anatomical and genetic points of convergence. The hypothalamus has emerged as a key brain area in several headache disorders including migraine and cluster headache. It is involved in homeostatic regulation, including pain processing and sleep regulation, enabling appropriate physiological responses to diverse stimuli. It is also a key integrator of circadian entrainment to light, in part regulated by pituitary adenylate cyclase-activating peptide (PACAP). With its established role in experimental headache research the peptide has been extensively studied in relation to headache in both humans and animals, however, there are only few studies investigating its effect on sleep in humans. Given its prominent role in circadian entrainment, established in preclinical research, and the ability of exogenous PACAP to trigger attacks experimentally, further research is very much warranted. The current review will focus on the role of the hypothalamus in the regulation of sleep-wake and circadian rhythms and provide suggestions for the future direction of such research, with a particular focus on PACAP.